Pelayanan Advokasi Bebas Rentenir Bagi Masyarakat Dhuafa Oleh Lembaga Sinergi Dompet Dhuafa Jabar Kota Bandung - Soni A. Nulhaqim (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2013)
In general, Moneylenders-Release Advocacy Service, conducted by DD Synergy Institute, is a service and advocacy for debt relief of poor people to moneylenders in Bandung and its surrounding areas. Moneylenders-release advocacy support can only be granted if the debt is used for living purposes (education, health and economic). Basically, this service is only advocating  poor people who have debts to loan sharks. This qualitative-approached research showed that the results of existing legal education implementation at Dompet Dhuafa Synergy Institute West Java has empowered clients, viewed from the perspective of client empowerment and strength, which is contained in one of the basic values of social work advocacy where the value is based on a belief that individuals have power to acquire knowledges. However, in the other hand, research found that client feel being watched by Dompet Dhuafa Synergy Institute West Java in every business, activity, and in fullfilling the needs of daily life. Keywords: kemiskinan, masyarakat dhuafa, rentenir, dan pelayanan advokasi.